SPIRITUAL QUOTIENT (SQ) DALAM ANALISIS NEUROLOGIS - Haeriyyah Haeriyyah (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2017)
Daniel Goleman once popularized the research of neurologist and psychologist who posted out that emotional intelligence is more decisive to life”s success than intellectual intelligence. He argues that EQ is a basiq requirement for using IQ effectively if parts of the brain to feel damaged then automatically can not think efectively. It turns out that at the end of the 20th century, a series of recent scientific data indicate the existence of spiritual intelligence that was tracked by neurologist. The need for God or spiritually is an invitable need for humanity. There is a direct and firm link between these needs and the availabity of divine potential in the human brain. Brain researches find the temporal region as a location that plays as important role in mystical and spiritual feelings. In this paper will present some reinforcing research evidences that strengthens the allegations of God’s spirituality and hardware in the human brain: 40 Hz oscillation, God Spot, cognitive subconscious, somatic marker.